AN ANALYSIS OF TRANSLATION TECHNIQUES USED IN THE SUBTITLE OF SHANG-CHI AND THE LEGEND OF THE TEN RINGS MOVIE - Dika Aristia Yuda; Nico Harared (PROJECT (Professional Journal of English Education), 2023)
The aim of this research is to classify and examine the translation techniques used in the subtitles of Shang Chi and the Legend of the Ten Rings movie, as well as the dominant strategy used by translators in translating English and Indonesian subtitles, using Molina and Albir translation techniques. In addition, other related theories are used in the research to support the analysis. This study's data was gathered and analyzed using qualitative descriptive techniques. This paper produced 508 data, including literal translation (193 data), linguistic compression (117 data), borrowing (65 data), established equivalent (60 data), modulation (16 data), discursive creation (16 data), linguistic amplification (12 data), variation (9 data), reduction (9 data), particularization (7 data), transposition (2 data), substitution (1 data), compensation (1 data), and description (1 data). And the most dominant strategy is literal translation (193 data). Keywords: Movie; Translation Technique; Subtitle